THE INFLUENCE OF PERFORMANCE-BASED BUDGETING PROCEDURES, EMOTIONAL INTELLIGENCE, AND INTERNAL CONTROL SYSTEM ON THE EFFECTIVENESS OF THE SUPERVISORY FUNCTION OF LEGISLATIVE MEMBERS IN DPRD OF GORONTALO CITY - Datau, Ramdan; Aneta, Asna; Hatu, Rauf A. (Universitas Negeri Gorontalo, 2020)
In this research, we analyzed the influence, either partial or simultaneous, of performance-based budgeting procedures, emotional intelligence, and internal control system on the effectiveness of the supervisory function of legislative members in the DPRD of Gorontalo City. This research used a quantitative approach. The research method was ex post facto. The research design was causality. The data analysis technique used was double regression. Findings indicate that (1) Performance-based budgeting procedures had a significant positive impact on the effectiveness of the supervisory function of legislative members in the Regional People’s Representative Council (DPRD) of Gorontalo City at a coefficient of determination of 44.50%, (2) Emotional intelligence had a significant positive impact on the effectiveness of the supervisory function of legislative members in the Regional People’s Representative Council (DPRD) of Gorontalo City at a coefficient of determination of 21.20%, (3) Internal control system had a significant positive impact on the effectiveness of the supervisory function of legislative members in the Regional People’s Representative Council (DPRD) of Gorontalo City at a coefficient of determination of 25.00%, and (4) Performance-based budgeting procedures, emotional intelligence, and internal control system simultaneously had a significant impact on the effectiveness of the supervisory function of legislative members in the Regional People’s Representative Council (DPRD) of Gorontalo City at a coefficient of determination of 90.70%. The rest, which was 9.30%, was elucidated by other variables unexplained in this research, e.g., bureaucratic structure, cooperative networking, political interest, work competency, and work environment within supervision.